Contesting International Law from Within: Conservative Leadership and the Erosion of the Non-Use of Force in the U.S. Capture of Nicolás Maduro - Muhammad Iqbal Yunazwardi; Erina Ikawati (Jurnal Ilmiah Hubungan Internasional, 2026)
This article examines how conservative leadership contests international legal norms through a qualitative case study using discourse analysis of the United States’ capture of Venezuelan President Nicolás Maduro under Donald Trump. Moving beyond the binary distinction between compliance and violation, the study employs the framework of norm contestation and norm robustness developed by Deitelhoff and Zimmermann to analyze challenges to the international legal order from within. The findings show that the U.S. did not formally withdraw from the international legal system but instead engaged in justificatory and applicatory contestation by reframing the principle of non-use of force as a form of transnational law enforcement. The analysis identifies three key discursive roles—norm violator, promoter, and resister—and examines how their interactions shape competing narratives of legitimacy. The article further demonstrates that contestation serves as a strategic alternative to exit, allowing states to maintain formal legitimacy and institutional membership while expanding policy autonomy and weakening the constraining effect of international law. In this sense, the erosion of the non-use of force norm occurs not through formal withdrawal, but through gradual discursive reinterpretation that undermines its robustness over time. This study contributes to the literature by linking leadership, discourse, and norm dynamics to explain how international law is incrementally weakened in contemporary global politics. Keywords: norm contestation, conservative leaders, non-use of violence, international law, national interests